2010
DOI: 10.1093/ageing/afq159
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of vitamin D deficiency in Dutch psychogeriatric nursing home residents by weekly half-body UVB exposure after showering: a pilot study

Abstract: an 8 week course of weekly, frontal half-body irradiation with UVB, at 0.5 MED, leads to an significant increase in 25(OH)D serum levels, but this period is too short to reach vitamin D sufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 22 publications
1
22
0
1
Order By: Relevance
“…A recent study with geriatric nursing home residents reported that weekly exposure to UVB lamps after showering resulted in a significant increase in serum levels of 25(OH) vitamin D [14]. Although sunlight exposure is an inexpensive and effective therapy [15,16], a cluster randomized controlled trial in the elderly reported poor adherence to the intervention [17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study with geriatric nursing home residents reported that weekly exposure to UVB lamps after showering resulted in a significant increase in serum levels of 25(OH) vitamin D [14]. Although sunlight exposure is an inexpensive and effective therapy [15,16], a cluster randomized controlled trial in the elderly reported poor adherence to the intervention [17].…”
Section: Discussionmentioning
confidence: 99%
“…Estas enfermedades son multifactoriales y la participación de vitD se mantiene aún en estudio 34 . Dentro de las potenciales herramientas profilácticas para enfrentar este riesgo de deficiencia de vitD están la práctica programada de exposición UVB durante los meses de invierno; en un grupo de la tercera edad en Noruega se logró mejorar las concentraciones de 25OHD 35 . Otra medida es la fortificación con vitD de algún alimento de alto consumo en la población objetivo (ej.…”
Section: Discussionunclassified
“…The positive effects of artificial UVB light on serum 25(OH)D levels in older adults have been demonstrated on multiple occasions; however, one limitation of these studies is that the results cannot be applied to a natural setting [15,16]. This study explored the effects of moderate sunlight exposure therapy in a natural setting as an additional vitamin D source for SNF older adult residents already receiving oral vitamin D from food and supplements.…”
Section: Serum 25(oh)d Levels and Vitamin D Statusmentioning
confidence: 99%
“…The majority of in vivo studies that analyze the effects of UVB light in humans rely on artificial sources, and their results may not be applicable to a natural setting [15][16][17][18]. Limited research has been conducted in the United States in which exposure to solar UVB light in a natural setting is studied as a strategy to improve vitamin D status in institutionalized older adults.…”
Section: Introductionmentioning
confidence: 99%